From Environmental to Comprehensive Security - Westing, Arthur H.; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
This work presents the evolution of the traditional concept of "national security" as military security to additionally embrace "environmental security" and then necessarily also "social (societal) security", thence to be termed "comprehensive human security". It accomplishes this primarily by presenting 11 of the author's own benchmark papers published between 1983 and 2010 (additionally providing bibliographic citations to a further 36 of the author's related publications during that period). The work stresses the importance of transfrontier (regional) cooperation, and also recognizes global overpopulation as a key impediment to achieving comprehensive human security.
National and International Security: An Evolving Concept -- The Author's Relevant Papers: A Selective Listing -- From Environmental Security to Comprehensive Security: A Necessary -- Regional Security: An Ecological Necessity -- Regional Security: Maritime Issues -- Regional Security: Transfrontier Cooperation -- Regional Security: The Case of the Korean Demilitarized Zone (DMZ) -- The Question of Globalization -- Environmental Refugees: A Stark Reminder -- Population: Perhaps the Basic Issue -- Glossary.
Keywords: Environmental sciences; Environmental law; Sustainable development; Environment; Environmental Law/Policy/Ecojustice.; Sustainable Development; International Relations; Security Science and Technology